Perancangan Aplikasi Edukasi Gizi sebagai Upaya Pencegahan Stunting pada Balita di Kegiatan Posyandu - Prasetyani, Henny; Trisetiyanto, Adi Nova; Hidayat, Umar (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Stunting is one of the issues in the health sector that is the focus of government programs. This is an urgent need for efforts to prevent stunting through nutritional education. Until now, the form of health service at posyandu is still just measuring height and weight, even though improving posyandu services can be done more than that, especially in preventing stunting through nutrition education. The service aims to improve posyandu health services. Improving services also requires tools that make it easier to provide nutrition education which will be carried out by posyandu cadres by designing an Android-based nutrition education application. The stages of implementing the nutrition education service are: (1) assisting cadres and parents so that this nutrition education can be implemented at Posyandu Melati 3 Baturejo Village and (2) creating a nutrition education application according to needs that make it easier for posyandu cadres and parents as a form of help Posyandu service facilities. The nutrition education application makes it easier for posyandu cadres and parents because the application only needs to input height and weight then the nutritional status will appear and nutrition education will appear in the form of food recommendations that match nutritional status. This application can improve health by preventing stunting.